The sound patterns of syntax - Erteschik-Shir, Nomi.; Rochman, Lisa. (Oxford : Oxford University Press, 2010)
Leading scholars address the issues surrounding the syntax-phonology interface. These principally concern whether the phonological component can influence syntax and if so how far and in what ways.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Syntax; Grammar, Comparative and general -- Phonology